Pregnancy outcomes of monochorionic diamniotic and dichorionic diamniotic twin pregnancies conceived by assisted reproductive technology and conceived naturally: a study based on chorionic comparison - Shuhua Liu; Qianhua Xu; Jingyu Qian; Dehong Liu; Bin Zhang; Xianxia Chen; Mingming Zheng (BMC, 2024)
Abstract Objective To evaluate monochorionic diamniotic (MCDA) and dichorionic diamniotic (DCDA) twin pregnancies conceived by assisted reproductive technology (ART) and conceived naturally. Methods We retrospectively analyzed the data on twin pregnancies conceived by ART from January 2015 to January 2022,and compared pregnancy outcomes of MCDA and DCDA twins conceived by ART with those of MCDA and DCDA twins conceived naturally, pregnancy outcomes between MCDA and DCDA twins conceived by ART, and pregnancy outcomes of DCT and TCT pregnancies reduced to DCDA pregnancies with those of DCDA pregnancies conceived naturally. Result MCDA pregnancies conceived by ART accounted for 4.21% of the total pregnancies conceived by ART and 43.81% of the total MCDA pregnancies. DCDA pregnancies conceived by ART accounted for 95.79% of the total pregnancies conceived by ART and 93.26% of the total DCDA pregnancies. Women with MCDA pregnancies conceived by ART had a higher premature delivery rate, lower neonatal weights, a higher placenta previa rate, and a lower twin survival rate than those with MCDA pregnancies conceived naturally (all p < 0.05). Women with DCDA pregnancies conceived naturally had lower rates of preterm birth, higher neonatal weights, and higher twin survival rates than women with DCDA pregnancies conceived by ART and those with DCT and TCT pregnancies reduced to DCDA pregnancies (all p < 0.05). Conclusion Our study confirms that the pregnancy outcomes of MCDA pregnancies conceived by ART are worse than those of MCDA pregnancies conceived naturally. Similarly, the pregnancy outcomes of naturally-conceived DCDA pregnancies are better than those of DCDA pregnancies conceived by ART and DCT and TCT pregnancies reduced to DCDA pregnancies.